SISTEM PENGATUR SUHU PADA MESIN PENETAS TELUR TIPE PORTABLE - Nelli Susanti; Endo Argo Kuncoro; Hersyamsi Hersyamsi (Universitas Sriwijaya, 2012)
The aim of wasÂ this research was manufacture of portable incubator machines with daily temperature control. The research was implemented in several stages are tool design and testing of tool. The design of tool consist of temperature control system design. The testing of tool was done 23 days, purposely is to know the percentage of eggs that hatched. The result of research showed that the all equipments of incubator and control system can work purposely that was to raise the temperature as desired. IncubatorÂ has capacity of 15 eggs and of 66.67% hatch egg.Â Key words : temperature control system design, eggs, temperature.